2019
DOI: 10.31083/j.jin.2019.01.118
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary exercise promotes neurotrophic factor and suppresses apoptosis in hippocampal ischemia

Abstract: J o u r n a l o f I n t e g r a t i v e N e u r o s c i e n c eThis is an open access article under the CC BY-NC 4.0 license (https://creativecommons.org/licenses/by-nc/4.0/) Previous studies have demonstrated that exercise facilitates recovery from ischemia. However, the mechanisms need to be further elucidated. The current investigation was designed to study the effect of voluntary exercise on cerebral ischemia and discuss possible mechanisms usingmiddle cerebral artery occlusion model. Rats were randomly al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Different modalities of swimming exercise are known to elicit a preconditioning effect [ 73 , 74 ], able to attenuate or reverse cerebral injury in the early stage after ischemia [ 75 ], and improve cognition [ 76 ]. Furthermore, NO production from the three NOS isoforms [ 77 ] and increased hydroxyl radical rate [ 78 ] triggered by aerobic exercise participate in the formation of associative and spatial memory [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different modalities of swimming exercise are known to elicit a preconditioning effect [ 73 , 74 ], able to attenuate or reverse cerebral injury in the early stage after ischemia [ 75 ], and improve cognition [ 76 ]. Furthermore, NO production from the three NOS isoforms [ 77 ] and increased hydroxyl radical rate [ 78 ] triggered by aerobic exercise participate in the formation of associative and spatial memory [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it effectively reduced the expression of caspase-3 and inhibited neuronal apoptosis ( Choi et al, 2013 ). Zhang et al (2019) . showed that voluntary wheel running inhibits cellular apoptosis by downregulating the Bax/Bcl-2 ratio and caspase-3 protein expression.…”
Section: Mechanism Of Exercise Preconditioning Induced Cerebral Ische...mentioning
confidence: 99%